CORRELATION BETWEEN LEARNING MOTIVATION AND PAI LEARNING ACHIEVEMENT IN STUDENTS - Fatahillah, Auliya’; Abdul Wafi, Muchammad Hasan (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
The purpose of this study (1) is to determine whether there is a relationship between Islamic Religious Education learning achievement and learning motivation at Paiton Islamic Middle School. (2) To find out the level of relationship between learning achievement in Islamic Religious Education and learning motivation in Paiton Islamic Middle School.This research method uses quantitative methods. The population in this study were all students of class VII at Paiton Islamic Middle School, totaling 160 students. While the sample is 80 students taken 50% of the total population. The data collection technique uses a questionnaire while the data analysis technique uses product moment analysis.The results of data analysis show that learning motivation has a significant relationship to learning achievement as indicated by the correlation coefficient value of 0.467. While the significant test of the r test obtained that the r count obtained was greater than rtable at a significance level of 5% = 0.219 and at a significance level of 1% = 0.286. Thus it can be said that r count > r table, both at the 5% and 1% significance level, then H is nil (Ho) is rejected and Ha is accepted. So it can be concluded that there is a positive relationship between learning motivation and student learning achievement in Islamic Religious Education subjects at Paiton Islamic Middle School. While the correlation coefficient is said to be moderate.